THE IMPACT OF THE BOGOR BLESSING PROGRAM ON BUSINESS INCOME: MSME MUSTAHIK IN BOGOR CITY - Praja Yusup, Erwanda; Kurnia, Tuti; Amin, Muhammad; Akbar, Gamal (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2024)
This study aims to determine the impact of MSME empowerment from productive zakat funds through the Bogor Berkah program implemented by BAZNAS Bogor City on mustahik MSME business income. The research method used is quantitative with multiple linear regression analysis method. The data collection method uses interviews and questionnaires. The results of the study partially show that the implementation of the Bogor Berkah program on business capital assistance, skills training, marketing practices and mentoring has a significant effect on the business income of mustahik MSMEs by increasing the income generated. While simultaneously the implementation of the Bogor Blessing program has a significant effect on the business income of mustahik MSMEs by increasing the income generated.Â Â Â